The effectiveness of child-centered group play therapy and narrative therapy on preschoolers' separation anxiety disorder and social-emotional behaviours - Zarra-Nezhad Maryam; Pakdaman Fatemeh; Moazami-Goodarzi Ali (Taylor and Francis Group, 2025)
This study examined the effectiveness of child-centered group play therapy (CCGPT) and narrative therapy in reducing separation anxiety disorder (SAD) and boosting social-emotional behaviours in early childhood (2.5-4-year-olds). An 8-week-randomized controlled trial design with three intervention groups, i.e. CCGPT, narrative therapy, and a combination of both interventions (i.e. combined group), and one control group that provided data at a pre-test and post-test, was adopted. A total of 48 children who showed signs of SAD participated in the study. Results showed that compared to the control group, CCGPT and combined group interventions showed a lower separation anxiety level. Children in all three intervention groups showed lower behavioural problems and higher prosocial behaviours than the control group. The findings suggest that the three interventions could be effective selective psychotherapy methods to promote social-emotional competencies. The CCGPT and combined group, particularly, were effective psychotherapy methods for reducing SAD in early childhood.